2012
DOI: 10.2320/matertrans.me201107
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Tensile Tests of Aluminum Foam Sandwich with Dense Steel Face Sheets by Friction Stir Processing Route

Abstract: An aluminum foam sandwich was fabricated by FSP route. In this process, both the fabrication of a foamable precursor and the metallurgical bonding between the precursor and a dense steel sheet can be simultaneously conducted. Although intermetallic compounds consisting of Fe 2 Al 5 and FeAl 3 were generated, tensile tests revealed that the bonding strength of the interface was relatively high compared with the tensile strength of the aluminum foam with a porosity of approximately 80%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 18 publications
0
20
0
1
Order By: Relevance
“…Although such an FeAl IMC layer may decrease the strength of the interface, it has been shown that the Al foam part in aluminum foam/dense steel composite structures 10) and aluminum foam core sandwich panels with dense steel face sheets 11) has even lower strength than the bonding interfaces. Therefore, this result is not considered to be a problem, even if the FeAl IMC layer formed has a thickness on the order of 10 µm.…”
Section: Al Foam/dense Steel Compositementioning
confidence: 99%
See 1 more Smart Citation
“…Although such an FeAl IMC layer may decrease the strength of the interface, it has been shown that the Al foam part in aluminum foam/dense steel composite structures 10) and aluminum foam core sandwich panels with dense steel face sheets 11) has even lower strength than the bonding interfaces. Therefore, this result is not considered to be a problem, even if the FeAl IMC layer formed has a thickness on the order of 10 µm.…”
Section: Al Foam/dense Steel Compositementioning
confidence: 99%
“…8) Clad bonding and friction stir welding have been tested as metal bonding methods to create adhesive-free composites. 8,10,11) These methods employ the precursor method 1216) of creating Al foam, described as follows. First, the precursor is manufactured by mixing a blowing agent powder with the aluminum base material.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figs. 1(b)1(d), the probe of a rotating tool was inserted into plates A and B, and multipass FSP of 5 lines © 4 passes was applied to obtain a larger precursor and to mix the gases and powders thoroughly 10,11) using an FSW machine (SHH204-720, Hitachi Setsubi Engineering Co., Ltd.). Moreover, as shown in Fig.…”
Section: Compression Specimens Of Porous Aluminummentioning
confidence: 99%
“…The AlFe IMC layer is hard and brittle 12,13) and is considered to greatly affect the strength of the bonding interface. Although the bonding strength of the interface was higher than the tensile strength of the aluminum foam of the AFS with a porosity of approximately 80% according to the results of a tensile test, 9) the relationship between the tensile strength of aluminum foam with various porosities and the bonding strength of the interface of the AFS has not yet been quantitatively investigated.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, using this process, we successfully fabricated an AFS of A1050 aluminum foam and SPCC low-carbon steel sheets with high porosity of approximately 80% and metallurgical bonding between the aluminum foam and dense steel face sheets. 9) However, along the entire interface of the AFS, an AlFe intermetallic compound (IMC) layer with a thickness of several tens of micrometers was generated. The AlFe IMC layer is hard and brittle 12,13) and is considered to greatly affect the strength of the bonding interface.…”
Section: Introductionmentioning
confidence: 99%